Application of productive research tasks in working with gifted students in teaching serbian language and literature - Stakić, Mirjana M.; Milovanović, Boško Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In the work we examine the possibility of application of productive research tasks in working with gifted students in teaching Serbian language and literature. Using specific examples of interpretations of literary works we show that productive research assignments encourage students’ creative and inventive expression, creativity, imagination and criticality and enable them to develop in accordance with their personality, individual preferences and abilities. In the examples of their use in problem solving, we determine how productive research tasks are conducive to gifted students who need to learn through problem solving and school work and to experience learning as a challenge. They present the basis for independent research, which allows gifted students to express their own creativity and the need to acquire new, challenging knowledge, and represent a powerful motivational tool that teachers can use in order to further develop their talent. Creative application of the productive research tasks in teaching Serbian language and literature is the possibility that the education of gifted students is not treated as elitist question, but to transform teaching process into development of giftedness and talent, where the role of the teacher in the teaching process rises to the role of the mentor.